Geotechnical Behavior of Helical Piles Via Physical Modeling by Frustum Confining Vessel (FCV) - Khazaei, Javad; Eslami, Abolfazl (International Journal of Geography and Geology, 2016)
Helical piles including central shaft and helices performance depends on soil properties, soil-pile interaction and the pile geometry. Failure due to helical piles axial loading can occur either in individual helix vicinity or cylindrical shear surface. So, the failure type can affect on piles behavior and also their capacity. Static analysis, in-situ testing records and also static or dynamic tests can be used for calculating of helical piles capacity. In this study we focused on an experimental method that carried out by frustum confining vessel (FCV) to investigate geotechnical behavior of helical piles. The FCV has been used because of its special geometry that makes a linear distribution of vertical and lateral stresses along its vertical line. Thus, it can simulate field conditions as well. Accordingly, several tests performed on small scale helical piles are made of 4 mm thick steel plate with 750 mm length, 32 mm shaft diameter and 64 to 89 mm helices diameter. According to the achievements, helical piles behavior essentially depends on pile geometric characteristics and in addition test results demonstrated the bearing capacity of helical model piles depends on spacing ratio, S/D, and helices diameter. Results also, indicated helical model piles can bear axial uplift loads about equal of usual steel model piles that have the helices diameter and in compression their bearing capacity is too sufficient to act as a medium pile.